الحركة العلمية المعاصرة في منطقة جارسده خيبر بختون خواه الباكستانية: The Educational movement in the Charsadda (Khyber pukhtoon khwah Pakistan) region in the modern era - Irfan Qaisar; Muhammad Yaseen; Dr. Haroon-Ur-Rashid (MEI, 2023)
The Educational movement in the Charsadda region in the modern era flourished widely, it seems so obvious in a number of Educational/scientific and cultural fields as a result of universal education and the spread of knowledge in the region. The importance of the region emerged from the cultural Charsadda Endowed Scholars/scientists who appeared on its territory, and they contributed to supporting the cultural movement throughout the country. And support and encourage and provide them with specialists from scholars’ science and literature, carrying the flares of science and knowledge in various fields and cognitive fields. This article will address the models of some of the efforts of those who contributed to the human civilization and scientific renaissance in the Charsadda region.